2022
DOI: 10.1093/pnasnexus/pgac219
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disadvantage, chronic stress, and proinflammatory phenotype: an integrative data analysis across the lifecourse

Abstract: Socioeconomic disadvantage confers risk for many chronic illnesses, and theories have highlighted chronic psychological stress and alterations to inflammatory processes as key pathways. Specifically, disadvantage can heighten chronic stress, which may promote a pro-inflammatory phenotype characterized by immune cells mounting exaggerated cytokine responses to challenge and being less sensitive to inhibitory signals. Importantly, lifecourse perspectives emphasize that such immune alterations should be more pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Symptomatic osteoarthritis is a cause of chronic stress because patients have difficulty in performing daily activities and may be socially isolated because of their disability to move, resulting in a low score in the QoL questionnaire. Indeed, increased chronic stress promotes a proinflammatory phenotype characterised by the ascendance of immune cells and elevated production of cytokines, accompanied by a reduction of inhibitory signals [ 20 ]. Additionally, recent experimental data in humans and animal models has shown that stress induces a hyperinflammatory state in myeloid cells that is accompanied by alterations in chromatin structure at inflammatory and metabolic gene loci, elevated expression of inflammatory genes, and increased cytokine secretion [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic osteoarthritis is a cause of chronic stress because patients have difficulty in performing daily activities and may be socially isolated because of their disability to move, resulting in a low score in the QoL questionnaire. Indeed, increased chronic stress promotes a proinflammatory phenotype characterised by the ascendance of immune cells and elevated production of cytokines, accompanied by a reduction of inhibitory signals [ 20 ]. Additionally, recent experimental data in humans and animal models has shown that stress induces a hyperinflammatory state in myeloid cells that is accompanied by alterations in chromatin structure at inflammatory and metabolic gene loci, elevated expression of inflammatory genes, and increased cytokine secretion [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The monocytes of children living in adversity also become less sensitive to inhibitory signals, such as glucocorticoids and primarily anti‐inflammatory cytokines (e.g. IL‐10), which further dysregulates the inflammatory response (Lam, Chen, Chiang, & Miller, 2022; Schreier, Roy, Frimer, & Chen, 2014). This insensitivity may be adaptive during acute threats but under conditions of chronic stress could facilitate low‐grade and nonresolving chronic inflammation (Miller et al., 2011).…”
Section: Inflammation In Depressionmentioning
confidence: 99%
“…Mechanistically, experiences of stress earlier in life are known to calibrate the response tendencies of innate immune cells so they mount excessive inflammatory responses to microbial challenges and become insensitive to glucocorticoid hormones that regulate these responses. 13,19 This response tendency has been termed a proinflammatory phenotype. 13 To assess proinflammatory phenotypes, we used a portable cell culture protocol developed for field settings, 33 where immune cells are incubated ex vivo with a bacterial product (lipopolysaccharide [LPS]), and production of the proinflammatory cytokines interleukin-1β, interleukin-6, and tumor necrosis factor-α were measured.…”
Section: Proinflammatory Phenotype (Age 31 Years)mentioning
confidence: 99%